La desnaturalización laboral en el sector público del Perú: el abuso en la contratación administrativa de servicios y mediante locación de servicios por el Estado - Brea Villanueva, Giorgio Gesú (2023)
The purpose of this research is to study the legal consequences of the situation of labor distortion in the Peruvian civil service, specifically, how the Peruvian legal system has responded to fraud and abuse of temporary and civil contracts in the Public Administration. From this, we arrive at the construction of our own position. For this, the principles that protect the subordinate employment relationship and those others that protect public employment have been reviewed in the first chapter, in addition it is exposed the current situation of informality with the statistical information that the state itself has produced. In the second chapter, the different responses that the norms and jurisprudence have given to the situation of labor informality in the public sector are exposed critically and in a comparative key. And, based on this information, in the third chapter, it is concluded that it is essential to face the problem of labor informality in the public sector, from a constitutional point of view, to strengthen, once and for all, a single civil service regime. But since this is a mediate measure, it is then stated that, given the conflicting interests of the worker and those who seek to protect a meritocratic public job at the service of the nation, entry into the public service cannot be granted if it is not through a public contest of merits in conditions of equality.